The Comparison of Long-term Effect Between Intermittent Fasting and Calorie Restriction on Neurological Parameters of Mice - Ni'ma, Neli Syahida; Anggadiredja, Kusnandar (Biology, Medicine, & Natural Product Chemistry, 2024)
Intermittent fasting (IF) and calorie restriction (CR) were purported to have health benefits. This research aimed to determine the long-term effect of IF and CR on selected neurological parameters in mice. Swiss Webster male mice were divided into 3 groups: ad libitum feeding (AL), IF, and CR. Mice in each group received the treatment for 16 weeks. They were then tested for anhedonia, depression, aggressiveness, and social approach. They were also subjected to contextual fear conditioning tests to model PTSD. Compared to AL, sucrose intake in the IF group was lower, while the CR group showed higher intake (p<0.01). This anhedonia characteristic shown in the IF group was confirmed not related to depression, as shown by significantly lower immobility time in the forced swimming test compared to AL (p<0.05). In the resident-intruder test, attack numbers in the IF group were fewer than in the AL group (p<0.05). As demonstrated by the results of the three-chamber test, the reduced aggressiveness in IF mice was unrelated to a deficit in sociability. In the fear extinction test (PTSD model), mice in the IF group showed lower freezing compared to those in AL (p<0.001). Although both IF and CR caused a reduction in total food intake, in the mice model tested, IF was shown to have favorable impacts on neurological parameters.